General meeting of funders on information technology-based joint funding services - Nurhilmiyah Nurhilmiyah (Indonesian Journal Education, 2026)
The rapid growth of financial technology (FinTech), particularly information technology–based lending services (peer-to-peer lending), has transformed the financing ecosystem by enabling direct interaction between lenders and borrowers through digital platforms. Despite this development, governance mechanisms that represent and protect the collective interests of funders remain limited within the regulatory framework. This study aims to analyze the legal position, functions, and potential regulatory framework of the General Meeting of Funders as a governance mechanism in information technology–based joint funding services. The research employs a normative juridical approach using statutory, conceptual, and comparative legal analyses. The findings indicate that the absence of a formal collective forum for funders may weaken transparency, accountability, and collective decision-making in digital lending platforms. The proposed concept of a General Meeting of Funders can function as a participatory governance mechanism that facilitates collective supervision, strengthens the accountability of platform operators, and enhances legal protection for funders. This study contributes to the development of regulatory frameworks for digital financial services by proposing a governance model that balances technological innovation with legal certainty and investor protection.